Reuse of CFRP Pultrusions in Novel Post-Tensioning Cables for Bridge Strengthening - Giovanni Pietro Terrasi; Christian Affolter; Gregor Schwegler; Andre Guerotto; Andreas Winistörfer (Buildings)
This paper presents the development and validation of a new filament-wound CFRP sleeve and resin grout for the efficient anchorage of parallel CFRP wire bundles. Twenty-five-year-old, reused CFRP wires (recovered from two dismantled bridge cables) were examined with regard to any possible drop in strength or stiffness due to aging and then processed into two bridge strengthening cables. The new anchorage and cables were tested to their tensile capacity (giving on average 1.833 MN) in two full-scale instrumented experiments. This being successful, it gave the authors the confidence to manufacture two new 26–30 m long post-tensioning parallel-wire cables, each using 37 of the recovered CFRP wires. Both CFRP parallel-wire cables were finally successfully prestressed to 1 MN (55% of their UTS) in order to strengthen an existing bridge in the Swiss Alps over the river Ilfis in the summer of 2023. This strengthening project is described. The full-scale tests confirmed the durability and strength of the new anchorage system, and the feasibility for reusing valuable CFRP pultrusions for post-tensioning was proven by the successful bridge strengthening carried out. Finally, the project also demonstrated the sustainability potential of CFRP pultrusions. The monitoring data of this bridge project are presented and discussed.